Marker assisted pyramiding of major blast resistance genes Pi9 and Pita in the genetic background of an elite Basmati rice variety, Pusa Basmati 1 - Khanna, Apurva; Sharma, Vinay; Ellur, Ranjith K; Shikari, Asif B.; Krishnan, S. Gopala; Singh, U.D.; Prakash, G.; Sharma, T.R.; Rathour, Rajeev; Variar, Mukund; Prashanthi, S.K.; Nagarajan, M.; et al. (The Indian Journal of Genetics and Plant Breeding, 2016)
Basmati is a premium quality rice of India which is highly priced in the international market. Pusa Basmati 1, an elite Basmati rice variety is highly susceptible to rice blast caused by Magnaporthe oryzae. Therefore, pyramiding blast resistance genes is essential to effectively combat the blast disease and increase the durability of resistance genes. The blast resistance genes Pi9 and Pita have been earlier demonstrated to be effective in Basmati growing regions of the country. Therefore, in the present study, monogenicnear isogenic lines Pusa 1637-18-7-6-20 and Pusa 1633-3-8- 8-16-1 carrying Pi9 and Pita, respectively, were intercrossed to generate pyramided lines through marker assisted foreground, background and phenotypic selection for recurrent parent phenotype. The pyramided lines carrying Pi9+Pita were found to be either at par or superior to the recurrent parent Pusa Basmati 1 for agro-morphological, grain and cooking quality traits. Further, these pyramided lines were also found to show resistance against three virulent pathotypes of M. oryzae namely, Mo-nwi-kash 1, Mo-nwi-lon2 and Mo-ei-ran1, when evaluated under artificial inoculation conditions as well as in the natural epiphytotic conditions of uniform blast nursery at two locations. The developed pyramided lines are the potential sources of blast resistance genes in the Basmati improvement program and can also be released for commercial cultivation after required testing.